Critical Analysis of Honest Character Strengthening with Honesty Canteen Media - Rismiati Rismiati; Wakhudin Wakhudin (Proceedings Series on Social Sciences & Humanities, 2023)
This study aims to describe the process of strengthening honest character with honesty canteen media to improve honest character in elementary school students. Preliminary observations show that students' awareness of the importance of honest character is still lacking and the application of honest character is not optimal. The method used in this research is a qualitative approach with case studies. The subjects in this study were fifth grade students at SDN Binangun 01 in Binangun District. Data collection techniques with interviews, observation, and documentation studies. Activities in data analysis are data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of the "Coin Cares for Friends" activity can improve the character of social care in elementary schools.